Study of Mangan Peroxidase (Mnp) Enzymes from Pleurotus Ostreatus Produced using Coffee Grounds and Rice Bran as Substrates through Response Surface Methodology - Mifthahul Jannah; Hermansyah Hermansyah; Poedji Loekitowati Hariani (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2025)
This study aimed to optimize the production of Manganese Peroxidase (MnP) enzyme from Pleurotus ostreatus using agricultural waste substrates such as coffee grounds (CG) and rice bran (RB) through Response Surface Methodology (RSM) approach. Optimization was conducted using a Central Composite Design (CCD) with three main variables, namely MnSO₄ concentration (0.5-1.5) mM, incubation temperature (25-35) °C, and reaction time (20-30) min. The enzyme fractionation process was carried out by ammonium sulfate saturation (0-20%), (20-40%), (40-60%), followed by dialysis, and SDS-PAGE analysis. The results showed that the 0-20% fraction of CG:RB (50:50) substrate had the highest enzyme activity, which was 20.588 ± 0.141 U/mL, with the highest specific activity of 76.967 ± 0.325 U/mg. The highest protein content was found in CG:RB (0:100) substrate at 0.825 ± 0.016 mg/mL. However, the enzyme activity was lower due to the presence of non-enzymatic proteins and natural inhibitors. This study successfully demonstrated that the substrate combination of CG:RB (50:50) provided optimal results for MnP production. The Response Surface Methodology proved effective in optimizing process variables, providing great potential for biotechnology applications using agricultural waste as an environmentally friendly raw material.Keywords: Pleurotus ostreatus, Manganese Peroxidase, Coffee Dregs, Rice Bran, RSM, SDS-PAGE